1994
DOI: 10.3171/jns.1994.80.6.0963
|View full text |Cite
|
Sign up to set email alerts
|

Cervical corpectomy and plate fixation for postlaminectomy kyphosis

Abstract: Between 1987 and 1991, 20 patients with symptomatic postlaminectomy kyphosis were treated with anterior decompression, bone graft, and anterior cervical plate. The patients were predominantly male (14:6) with a mean age of 58 years. The initial laminectomy was performed for either spondylosis (80%) or spinal tumor (20%). All patients had anterior compressive pathology, which was associated with instability (45%), neck pain (75%), myeloradiculopathy (90%), or severe neck deformity (30%). The mean degree of kyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
123
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(129 citation statements)
references
References 27 publications
1
123
1
3
Order By: Relevance
“…As to correction angles of kyphotic deformity in the cervical spine treated by anterior procedures, Ferch et al [27] reported the preoperative kyphosis was 10°and correction was 11°on average. Herman et al [13] reported that their kyphosis correction was 21°on average. Both studies did not report any postoperative late neurological complications.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As to correction angles of kyphotic deformity in the cervical spine treated by anterior procedures, Ferch et al [27] reported the preoperative kyphosis was 10°and correction was 11°on average. Herman et al [13] reported that their kyphosis correction was 21°on average. Both studies did not report any postoperative late neurological complications.…”
Section: Discussionmentioning
confidence: 96%
“…For kyphosis correction of the cervical spine, some surgeons select the anterior procedure [13,14], whereas other surgeons choose the posterior [15,16] or a combination of anterior and posterior approaches [17,18]. In posterior cervical reconstruction surgery, postoperative neurological deficits unrelated to instrument malpositioning or hematoma formation have been reported by some authors [8,[19][20][21] Heller et al [8] reported 2 (2.7%) cases with this complication after posterior cervical reconstruction surgery using lateral mass screws and plates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications include degenerative disorders, [1][2][3] neoplasms, 4-5 trauma, [6][7] infectious disorders, 8 or correction of either degenerative or iatrogenic kyphosis. [9][10][11][12] The procedure has enjoyed excellent clinical results, in terms of neurological outcomes, and success of arthrodesis and stabilization. 2,9,[13][14][15][16] Fusion of the cervical spine has biomechanical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The procedure has enjoyed excellent clinical results, in terms of neurological outcomes, and success of arthrodesis and stabilization. 2,9,[13][14][15][16] Fusion of the cervical spine has biomechanical consequences. Loss of mobility at one functional spinal unit increases the load sustained by the remaining units.…”
Section: Introductionmentioning
confidence: 99%